MRI-FI-guided superimposed stimulus-responsive co-assembled liposomes for optimizing transmembrane drug delivery pathways and improving cancer efficacy. (March 2022) - Liu, Chenyu; Chen, Hailiang; Zhou, Hengjun; Yu, Simiao; Zhao, Yu; Wang, Ning; Yao, Weihe; Lu, An-Hui; Qiao, Weihong
Highlights: Multi-stimulus superimposed response strategy of GFC liposomes is guided by precise and real-time MRI-FI imaging. GFC liposomes can intelligently optimize transmembrane drug delivery pathways based on actual received stimulus. Triggered GFC liposomes have membrane fusion capability and their response to stimulation follows dissociation-fusion-rearrangement-fragmentation mechanism. Abstract: Cancer is a serious challenge for humanity and the key to advancing cancer therapy is to increase cellular uptake of drugs. This paper provides a folic acid GFC liposome that relies on magnetic resonance imaging-fluorescence imaging (MRI-FI) to precisely guide the multi-stimulus response at the tumor site. By accurately increasing the concentration of free drug at the tumor site, it promotes the efficient diffusion of small molecule drugs into cells and penetration into solid tumors. Furthermore, based on the stimulus response mechanism of GFC liposomes (dissociation-fusion-rearrangement-fragmentation), we demonstrated that GFC liposomes can optimize the high-energy unfavorable fusion behavior of liposomes with cell membranes. In this way, GFC liposomes can intelligently and efficiently deliver drugs into cells in the form of active endocytosis, spontaneous membrane fusion and diffusion, depending on the actual stimulus response effect. Finally, animal experiments demonstrated the potential of the highly efficient MRI-FI-based GFC carrier with a 9.13-fold tumor suppression efficiency. Herein, this paper highlights the advantages of MRI-FI-guided precise multi-stimulus-controlled release and high uptake rate strategies to provide ingenious and concise ideas for precise and efficient cancer therapy. Graphical abstract: Image, graphical abstract